Cisza i milczenie: aktualność propozycji chrześcijańskiej - Misztal, Wojciech (Analecta Cracoviensia, 2013)
The article presents the topicality of the Christian approach to the quiet and the silence. Christian spirituality has been characterized by a realistic and balanced treatment of the human person who is a being in need of both quiet and silence, as well as an exchange of information. Then attention has been focused on the needs and the potential of contemporary society. In such a context the importance of quiet and silence in case of the contemporary society has been presented as a positively important, even essential element of the fruitful creation of their offer and, subsequently, taking advantage of it.